2020
DOI: 10.1186/s12893-020-00897-3
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal natural orifice transluminal endoscopic surgery (vNOTES) hysterectomy for uterus weighing ≥1 kg

Abstract: Background The transvaginal natural orifice transluminal endoscopic surgery (vNOTES) applied in gynecology has been developed recent years and been evolving. In this study, we aimed to evaluate the feasibility and effect of the vNOTES hysterectomy for uterus ≥1 kilogram (kg). Methods From January 2019 to March 2020, patients with benign indications in cases of uterus weighing ≥1 kg, underwent vNOTES hysterectomy were studied retrospectively. The patients’ demographics, indications for surgery, operation outc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Currently, there are no published studies available to address the learning curves of R‐vNOTES for hysterectomy through two different methodologies. Previous data demonstrate that the surgeon’s learning curve for traditional vNOTES hysterectomy in benign gynecology was approximately 10–25 cases, 21,34,35 and 9–50 cases were needed to achieve stability for robotic‐assisted hysterectomy 31,34,36,37 . Since total operative time is greatly affected due to additional surgical procedures, we created the learning curve based on the robot docking time, port placement time and hysterectomy times in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no published studies available to address the learning curves of R‐vNOTES for hysterectomy through two different methodologies. Previous data demonstrate that the surgeon’s learning curve for traditional vNOTES hysterectomy in benign gynecology was approximately 10–25 cases, 21,34,35 and 9–50 cases were needed to achieve stability for robotic‐assisted hysterectomy 31,34,36,37 . Since total operative time is greatly affected due to additional surgical procedures, we created the learning curve based on the robot docking time, port placement time and hysterectomy times in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data demonstrate that the surgeon's learning curve for traditional vNOTES hysterectomy in benign gynecology was approximately 10-25 cases, 21,34,35 and 9-50 cases were needed to achieve stability for robotic-assisted hysterectomy. 31,34,36,37 Since total operative time is greatly affected due to additional surgical procedures, we created the learning curve based on the robot docking time, port placement time and hysterectomy times in this study. The 84 cases in this study were all completed by a single experienced gynaecologic surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 39 were excluded because they did not meet eligibility criteria. Thus, 116 studies were included in the final analysis, 11,23–137 including 15 RCTs, 17 nonrandomized comparative studies, and 84 single-group studies (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study of VNH for uterine weight ≥280 g had one conversion to laparotomy for specimen extraction, however, VNH was successful with uterine weight up to 3361 g [12 ▪ ]. A study of VNH for uteri ≥1 kg reported a high rate of conversion (7.7%), however, the secondary approach was traditional laparoscopy, and laparotomy was avoided in all cases [13 ▪ ]. In comparative studies of patients with large uteri, VNH was favorable over TLH for operative time, hospitalization, and postoperative pain scores with similar blood loss and complications [14 ▪ ].…”
Section: Surgical Applicationsmentioning
confidence: 99%